Chest CT screening for COVID-19 in elective and emergency surgical patients: experience from a UK tertiary centre. Issue 8 (August 2020) - Chetan, M.R.; Tsakok, M.T.; Shaw, R.; Xie, C.; Watson, R.A.; Wing, L.; Peschl, H.; Benamore, R.; MacLeod, F.; Gleeson, F.V.
Abstract : AIM: To determine the incidence of possible COVID-19-related lung changes on preoperative screening computed tomography (CT) for COVID-19 and how their findings influenced decision-making. To also to determine whether the patients were managed as COVID-19 patients after their imaging findings, and the proportion who had SARS-CoV2 reverse transcriptionpolymerase chain reaction (RT-PCR) testing. MATERIALS AND METHODS: A retrospective study was undertaken of consecutive patients having imaging prior to urgent elective surgery ( n =156) or acute abdominal imaging ( n =283). Lung findings were categorised according to the British Society of Thoracic Imaging (BSTI) guidelines. RT-PCR testing, management, and outcomes were determined from the electronic patient records. RESULTS: 3% (13/439) of CT examinations demonstrated findings of classic/probable COVID-19 pneumonia, whilst 4% (19/439) had findings indeterminate for COVID-19. Of the total cohort, 1.6% (7/439) subsequently had confirmed RT-PCR-positive COVID-19. Importantly, all the patients with a normal chest or alternative diagnoses on CT who had PCR testing within the next 7 days, had a negative RT-PCR (92/407). There was a change in surgical outcome in 6% (10/156) of the elective surgical cohort with no change to surgical management was demonstrated in the acute abdominal emergency cohort requiring surgery (2/283). CONCLUSION: There was a 7% (32/439) incidence of potential COVID-19-related lung changes in patients having preoperative CT. Although this altered surgical management in the elective surgical cohort, no change to surgical management was demonstrated in the acute abdominal emergency cohort requiring surgery. Highlights: 7% incidence of classic/probable or indeterminate COVID-19 in pre-operative CT screening. Change in surgical management in 6% elective surgical cohort. No change to surgical management in the acute abdominal emergency cohort requiring surgery. No patient with a normal chest or alternative diagnosis on CT had a subsequent positive PCR result.